In-situ observation of convection in droplet under microwave radiation by PIV - Asada, M.; Kanazawa, Y.; Asakum, Y.; Honda, I.; Phan, Chi; Parmar, Harisinh Bhikhubhai; Pareek, Vishnu; Evans, G. (S P I E - International Society for Optical Engineering, 2014)
In this study, microwave irradiation is applied to a liquid droplet and the surface tension, the circulation flow and temperature of water droplet are measured dynamically under the irradiation. The droplet was allowed to return to its original temperature after the irradiation, it was found that water surface tension remained well below its original value for an extended period of time. Surface tension reduction shown similar effect of "impurity" at molecular level during the microwave, and some "memory" after microwave, which might be caused by nano-bubble. On the other hand, microwave can introduce the circulation flow of higher rotation speed and will be expected to be applied for non-contact stirring method.